Utilization efficiency of microwave energy for granular food in continuous drying: From propagation properties to technology parameters. Issue 9 (12th July 2022) - Wang, Lei; Zhao, Yueming; Ma, Wenyu; Shen, Liuyang; Liu, Chenghai; Liu, Chai; Zheng, Xianzhe; Li, Shilei
Abstract: To elucidate the utilization efficiency of microwave energy (UEME) of granular food, germinated brown rice (GBR) as a representational material, in a continuous microwave dryer, the propagation of microwave energy inside drying cavity and the effects of technology parameters on the energy consumption of GBR material layer were investigated by using numerical simulation and bench experiments. Results indicate that the transmission loss of microwave scatter from the waveguide ports decline with the increase of thickness of grain layer in drying cavity. The total absorption of microwave energy is achieved in the thickness of material processed exceeding critical depth of microwave penetration to reduce the scatter loss of microwave transmission. In microwave cavity, the dissipation of microwave energy inside material processed alters the modes and frequency of microwave propagation and resonance, and continuous movement and ventilation process may promote UEME due to the improvement of drying uniformity of GBR. High UEME may be achieved at the temperature of GBR material layer in range of 100 ± 5 °C till final moisture content of 14.5% ( w.b. ). The optimal technology parameters of microwave drying for GBR is obtained as microwave intensity of 2 W/g, ventilation velocity of 1.0–1.5 m/s, drying duration for per drying pass of 6 min, and the thickness of GBR layer of 8 mm to achieve high UEME. The research results provide significant insights to evaluate the electric field distribution and design industrial microwave dryer with high utilization efficiency of microwave energy.